Wayfinding design a case study on the efficiency of the wayfinding systems in the public markets of Davao City - Del Puerto, Shaira A.; Regalado, Angelo Felix N. (2018)
Markets have always been regarded as one that sparks urban revitalization. As it is a public space, it provides not only for the economy but also to the public?s social needs. By observing how the public market customers react to the environment of the public market, it can be evaluated how efficient the public market is. Thus, for this research, it will be its prime interest to understand the process of wayfinding common among the public market visitors. Only aspects for wayfinding that require visual cognition were surveyed and studied: Environmental information, spatial configuration, and experience. The research aims to determine whether the existing wayfinding system in Agdao, Bankerohan, and Toril public markets are efficient in providing for its customers. This was achieved by (1) understanding the wayfinding patterns of first-time customers as they experience the spaces first-hand, (2) the identification of signages and landmarks, (3) and determining these factors? relationship with each other and to the public market?s spatial configuration. The wayfinding data was analysed using the principles of space syntax with the aid of Depthmap simulated axial maps and Visibility Graph Analysis. The research was able to reveal how the arrangements of the spaces influence the wayfinding process in the public market ? how movement is highly influenced by the configuration of the spaces. Furthermore, pauses in the public market were found to occur in spaces with high visual information. Most of the wayfinding decision-making happened in these areas.
Thesis (BS Architecture) -- University of the Philippines Mindanao, 2018